Monitoreo continuo de glucosa en tiempo real y mejora del control glicémico en diabetes gestacional - Morales, María Del Mar (2022)
Appropriate glycemic control during pregnancy prevents maternal-fetal complications. Continuous Glucose Monitoring (CGM) devices measure interstitial glucose levels, allowing patients and providers observe glucose values in real time. There are clear benefits of this tool, but lack of clinical experience in Peru. Three pregnant women with gestational diabetes were managed with the help of the CGM, along with nutritional education sessions and medical check-ups with an endocrinologist. All pregnant women had adequate glycemic control with the use of CGM. Two of them required insulin treatment and nutritional counseling, while the other only required nutritional management. The CGM was well received by the patients because it helped in the recognition and counting of carbohydrates, as well as in the adjustment of the treatment.